Is there a choice to make? A pilot study investigating attitudes towards treatment in an Early Intervention for Psychosis service. Issue 2 (17th May 2018) - Cowdrey, Felicity Ann; Hogg, Lorna; Chapman, Kate
Abstract : Purpose: The purpose of this paper is to investigate health care professionals' (HCPs) and service-users' (SUs) attitudes towards different treatment options in an Early Intervention for Psychosis (EIP) service as well as the topical issue of offering choice over treatment. Design/methodology/approach: Seven SUs accessing an EIP service and nine HCPs completed qualitative surveys about treatment for psychosis. Data were analysed thematically. Findings: Both HCPs and SUs appeared to have a generally positive attitude to the range of interventions offered by the EIP service and SUs talked about the importance of all treatment options being explored. There was variation in attitudes towards SUs having choice over their treatment and a number of factors were identified as crucial in influencing attitudes including mental capacity, risk and level of engagement. Research limitations/implications: Small sample size, recruitment from only one EIP service and using a survey design limit generalisability and depth of analysis. Practical implications: HCPs working in EIP services should explore different treatment options fully with SUs but be aware that they may feel unable to make the decision themselves. Such discussions should be revisited throughout an individual's care as their ability and desire to make informed choices may change over time. Continuing Professional Development and clinical supervision should be used to help HCPs reflect on the choice agenda and the implications of this for clinical practice. Originality/value: Few studies have examined attitudes towards treatments for psychosis. This is an evolving and important clinical area that remains under researched. Recommendations for service-development, future research and clinical practice are made.